Role of Leadership in Facilitating Healing and Renewal in Times of Organizational Trauma and Change - Byrd-Poller, Lynda (IGI Global, 2021)
Organizational trauma theory endeavors to examine the psychological and physical effects of trauma on individuals and groups within an organization. Individual trauma, the individual mental and emotional disruptions that affect the well-being of self, often contributes to organizational trauma. Or sometimes, the disruptions are external and caused by societal, economic, or political changes. Recent traumatic events such as the COVID-19 pandemic and racial tensions stemming from social injustices present even greater challenges for organizations as leaders seek to facilitate healing, restoratio.